Growth and Yield Attributes of Wheat and Paddy Intercropped under Dalbergia sissoo Roxb. Based Agri-Silvicultural System on Partially Improved Salt Affected Soil in Faizabad District - Rao, O. P.; Sirohi, Chhavi; Verma, S. K. (Indian Forester, 2016)
A field experiment was conducted to evaluate the growth and yield of wheat and paddy under four year old Dalbergia sissoo based agri-silviculture system on sodic soil in eastern Uttar Pradesh. The experiment was laid out with treatment consisting of three varieties of wheat (NW-1067, NW-1014 and HD-2643) and paddy (Sarjoo-52, Narendra Usar-2 and Narendra Usar-3) grown in factorial Randomized Block Design. The study reveals that plant height (89.33 cm and 98.00 cm) and straw yield (1.15 t ha-1 and 1.59 t ha-1) varieties of wheat HD-2643 and paddy Narendra Usar-2 were found better respectively, when the crop were grown at 1.0 m away from D. sissoo tree base in the alley cropping. However, maximum number of per ear/panicle and 1000 grain test weight (grain yield 2.32 t ha-1 and 2.33 t ha-1) varieties of wheat NW-1067 and paddy Narendra Usar-2 were recorded respectively, when crop were grown in open area. Amongst different varieties viz. NW-1067 (wheat) and Narendra Usar-2 (paddy) were found better for cultivation under D. sissoo based agri-silviculture system. Wheat variety-NW 1067 and paddy variety Narendra Usar-2 were found better for cultivation under D. sissoo based agri-silviculture system in salt affected soil.